PERAN NGO KONTRAS â€œKOMISI UNTUK ORANG HILANG DAN KORBAN TINDAK KEKERASANâ€ DALAM MENDORONG PEMERINTAH INDONESIA UNTUK BERSIKAP TEGAS TERHADAP KASUS PELANGGARAN HAM ETNIS ROHINGYA DI MYANMAR TAHUN 200 - Nanang Khoirino (HI 16 UMY 071, 2016)
*71 This study will discribe the steps of advocacy of human rights committed by KontraS against the Rohingya in Myanmar.KontraS as ahuman rights NGO in Indonesia was able to advocate against human rights violations that occured in other countries. Through a multi track diplomacy, KontraS encourage Indonesia to actively take part in the resolution of human rights issue affecting the Rohingya people in Burma. KontraS also take advantages of transnational advocacy networks as a form of responsibility of the human rights NGO against human rights crisis in other countries.